286 Evaluation of the Lactose Level and Organic Acid Inclusion in Newly Weaned Pigs. (10th April 2018) - Graham, A; Greiner, L; Knopf, B; Goncalves, M A D; Cast, W; Orlando, U A D
Abstract: One thousand two hundred PIC (337 × Camborough; PIC, Hendersonville, TN) barrows and gilts were used to evaluate lactose levels and organic acid inclusion in newly weaned nursery pigs. At the start of the study, the pigs averaged 6.09 kg. The lightest 10% of pigs were sorted off to form one replication and the remaining pigs were sorted by gender and placed into blocks with 25 pigs per pen. Blocks were set for the 6 treatments (7.5% lactose, 7.5% lactose + 0.5% Activate (Novus International, St. Louis, MO), 12.5% lactose, 12.5% lactose + 0.5% Activate, 17.5% lactose, and 17.5% lactose + 0.5% Activate for phase 1; 3.8% lactose, 3.8% lactose + 0.5% Activate, 6.3% lactose, 6.3% lactose + 0.5% Activate, 8.8% lactose, and 8.8% lactose + 0.5% Activate for phase 2) within gender of similar weights with the block. All other nutrients met or exceeded the NRC (2012) recommendations. Pen weights and feed intake information were collected at the start and end of the phase to allow for calculation of ADG, ADFI, and G:F. Data were analyzed as a 2 X 3 factorial design using the PROC MIXED procedure of SAS with pen as the experimental unit, treatment as a fixed effect, and block as the random effect. Results were considered significant at P ≤ 0.05 and considered a trend at P > 0.05 and P ≤ 0.10. From 0 to 7 d, increasing lactose (7.5% to 17.5%) resulted in a significant improvement in ADG (0.07, 0.07, 0.09, 0.08, 0.09, 0.09 kg/d, respectively) and gain to feed (2.38, 1.74, 1.70, 1.68, 1.32, 1.60, respectively). Piglet weight at day 21 (12.67, 12.62, 13.06, 12.84, 12.91, 13.02 kg, respectively) and ADG (0.43, 0.43, 0.45, 0.44, 0.44, 0.45 kg/d, respectively) was significantly improved when lactose increased from 3.8% to either 6.3% or 8.8%. Overall, the use of higher lactose levels resulted in improved average daily gain. In conclusion, the data demonstrates that lactose levels above 7.5% in phase 1 and 6.3% in phase 2 result in improved nursery pig ADG while the use of an acidifier did not alter performance.